Back Cover. Issue 1 (18th February 2021) - Unknown
Abstract : A fully transient, safe and wearable power source can help reduce electronic wastes. In article number EOM212073, Zifeng Wang and co‐workers reported a fully degradable battery made entirely of environmentally friendly materials, such as fruit juice, gelatin, and cellulose. Using kirigami techniques, the device exhibits good mechanical flexibility against bending, twisting, and stretching. The proposed battery shows promising application in powering various wearable sensors. Abstract : A fully transient, safe and wearable power source can help reduce electronic wastes. In article number EOM212073, Zifeng Wang and co‐workers reported a fully degradable battery made entirely of environmentally friendly materials, such as fruit juice, gelatin, and cellulose. Using kirigami techniques, the device exhibits good mechanical flexibility against bending, twisting, and stretching. The proposed battery shows promising application in powering various wearable sensors.